Komunikasi Interpersonal Kepala Desa Dalam Membina Organisasi Kepemudaan Di Desa Karang Anyar - Izky Rahmayani (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
The village head has a very important role in mobilizing the participation of the younger generation in the field of development. However, there are several obstacles experienced by the community or youth organizations in carrying out these activities, including the lack of socialization carried out by the village head and the lack of communication links that are carried out so that it becomes an attraction for researchers to want to conduct research on how a village head is able to be close to youth organizations. The focus of this study was to find out how the village head's interpersonal communication in fostering youth organizations and what factors were supporting and inhibiting the village head's interpersonal communication in fostering youth organizations. The research method used in this research is descriptive qualitative research. Data collection techniques using the method of observation, interviews and documentation. Based on the results of the research obtained, it shows that interpersonal communication carried out by the Karang Anyar Village Head in fostering youth organizations by establishing friendships in the form of direct meetings and sharing to discuss and provide direction with youth so that the youth organization will be even better in the future. While the supporting factor is the use of appropriate language for youth, who have different levels of understanding. The obstacle faced by the village head was the difficulty in understanding the different characters possessed by each youth.